(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This review examines the profound influence of media on political decision-making processes. Media plays a pivotal role in shaping public opinion, influencing voter perceptions, and framing political agendas. Through extensive analysis of literature and case studies, this study explores how various forms of media, including traditional outlets and digital platforms, impact the decision-making dynamics of political leaders and institutions. Key factors such as media bias, agenda-setting effects, and the role of social media in political discourse are critically assessed. Understanding these influences is crucial for comprehending the complexities of contemporary political environments and their implications for democratic governance. By synthesizing insights from academic research and real-world examples, this review provides valuable perspectives on the evolving relationship between media and political decision-making, offering implications for policymakers, media professionals, and researchers alike.